The Cambridge economic history of modern Britain. Volume I, 1700-1870 - Floud, Roderick; Humphries, Jane; Johnson, Paul (Paul A.) (Cambridge : Cambridge University Press, 2014)
A new edition of the leading textbook on the economic history of Britain since industrialization. Combining the expertise of more than thirty leading historians and economists, Volume 1 tracks Britain's economic history in the period ranging from 1700 to 1870 from industrialisation to global trade and empire. Each chapter provides a clear guide to the major controversies in the field and students are shown how to connect historical evidence with economic theory and apply quantitative methods. New approaches are proposed to classic issues such as the causes and consequences of industrialisation, the role of institutions and the state, and the transition from an organic to an inorganic economy, as well as introducing new issues such as globalisation, convergence and divergence, the role of science, technology and invention, and the growth of consumerism. Throughout the volume, British experience is set within an international context and its performance benchmarked against its global competitors.
The British Industrial Revolution in a European mirror / Brian A'Hearn -- Occupational structure and population change / Leigh Shaw-Taylor and E. A. Wrigley -- Agriculture, 1700-1870 / Joyce Burnette -- Nutrition and health, 1700-1870 / David Meredith and Deborah Oxley -- Regions / Nigel Goose -- Labour markets and training / Patrick Wallis -- Inequality and social mobility in the era of the industrial revolution / Gregory Clark and Neil Cummins -- Consumption, 1700-1870 / Sara Horrell -- An age of progress / Joel Mokyr -- Technology / Robert Allen -- The financial revolution and its consequences / Anne L. Murphy -- Political power and British economic life, 1650-1870 / Julian Hoppit -- The transport revolution in industrialising Britain / Dan Bogart -- Overseas trade and empire / Nuala Zahedieh -- Economic ideas and the emergence of political economy / Roger E. Backhouse and Keith Tribe.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Great Britain -- Economic conditions; Great Britain -- Economic conditions -- 18th century; Great Britain -- Economic conditions -- 19th century